Characterization of the KRas G12D-inhibitor interactions by differential HDX-MS and molecular dynamics simulations - Evgeniy V. Petrotchenko; Brandon Novy; Edith Nagy; Konstantin I. Popov; Jason B. Cross; Roopa Thapar; Christoph H. Borchers (Computational and Structural Biotechnology Journal)
Hydrogen-deuterium exchange (HDX) combined with mass spectrometry (MS) is a powerful technique for studying changes in protein structure and dynamics upon ligand binding. Protein-ligand complexes can result in increased protection of peptide-bond amides in HDX indicating protein structure stabilization. We have characterized the interaction of small-molecule inhibitors towards the KRas G12D oncoprotein by intact-protein and bottom-up HDX-MS, in combination with molecular dynamics (MD) simulations. Significant differences in HDX protection were detected upon inhibitor binding in the flexible switch-II pocket of the protein. MD simulations of the free and inhibitor-bound KRas G12D proteins also revealed changes in the hydrogen bond network of backbone amides in the switch-II region upon inhibitor binding, explaining the observed HDX protection changes. We have proposed simple semi-empirical metrics which relate changes in HDX-MS experimental values and observed in MD simulations changes in individual backbone hydrogen-bonds between free- and ligand-bound protein states. This combined HDX-MS and MD approach provides an atomistic picture of changes in the KRas G12D secondary structure upon ligand binding and may be a useful tool for future drug design efforts.